Long-acting low-surface-energy coating with high recoatability as well as preparation method and application of long-acting low-surface-energy coating

By combining the alkane treatment agent and amino treatment agent to modify inorganic/organic nanoparticles, the coating surface micro-nano structure and hydrophilic-hydrophobic conversion structure are constructed, and problems such as cumbersome and inadequate green and environmentally friendly exist in the preparation process of existing low-surface energy coatings are solved, and low-surface energy coatings with high recoating performance and long-term effectiveness are achieved.

CN119708953AActive Publication Date: 2025-03-28SICHUAN UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411861198.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing low-surface energy coatings have problems such as cumbersome processes, insufficient green and environmental protection, single substrate selection, and limited application scope during the preparation process, making it difficult to achieve high recoating performance and long-term effectiveness.

Method used

The inorganic/organic nanoparticles are modified by alkane treatment agents and amino treatment agents, and the micro-nano structure of the coating surface and the introduction of hydrophilic-hydrophobic conversion structures are formed to form a long-term low-surface energy coating with high recoating performance. The method includes dispersing modified nanoparticles in an acidic solution, then adding an alkaline solution to restore neutrality, adding a matrix resin for coating, and mixing evenly to prepare the coating.

Benefits of technology

The superhydrophobicity, environmental adaptability and pH responsiveness of the coating are realized, the mechanical stability and recoating properties of the coating are improved, the service life of the coating is extended, and the preparation process is simple, green and environmentally friendly, and is suitable for a variety of substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708953A_ABST
    Figure CN119708953A_ABST
Patent Text Reader

Abstract

The invention provides a long-acting low-surface-energy coating with high recoatability as well as a preparation method and application of the long-acting low-surface-energy coating. The coating is mainly prepared from the following components in parts by mass: 0.1-5 parts of inorganic / organic nanoparticles jointly modified by an alkane treating agent and an amino treating agent, 0.2-10 parts of matrix resin for the coating and 85-99.7 parts of an aqueous solvent. The preparation method disclosed by the invention is simple in process, mild in condition, green and environment-friendly, and free of complex instruments and equipment, meanwhile, the formed coating also has relatively good super-hydrophobicity, environmental adaptability and pH responsiveness, and is endowed with high recoatability, and the service life of the coating is prolonged; and when the coating is locally damaged or aged after being used for a long time, a new coating can be obtained through re-coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of low surface energy coatings, and relates to a long-lasting low surface energy coating with high recoatability, and a preparation method and application thereof. Background Art

[0002] In recent years, my country's construction industry has developed rapidly. As one of the most important consumables in the construction and other industries, promoting its green and low-carbon manufacturing and application is of great significance to promoting the sustainable development of construction and other livelihood industries. However, traditional coatings have gradually exposed their shortcomings in mechanical stability, environmental adaptability, and recoatability. On the one hand, they are susceptible to yellowing, powdering, blistering, etc. in the long-term service process due to the influence of rain, acid and alkali, ultraviolet, temperature change, mold, etc. in the environment, or are susceptible to physical damage such as friction and adhesion, resulting in local damage, which ultimately leads to a significant reduction in performance and a large amount of subsequent maintenance costs; on the other hand, in the renovation process of old coatings, it is usually necessary to remove the entire coating and recoat a new coating, which not only consumes a lot of manpower and material resources, but also causes serious waste of resources and environmental pollution. Therefore, it is of great significance to develop low-surface energy coatings that have both mechanical stability, environmental adaptability and recoatability.

[0003] The Chinese patent of publication number CN110295000B discloses a method for preparing a low-viscosity and high-film-thickness polyvinyl ester coating that can be recoated. The modified vinyl ester resin is first prepared by using a vinyl ester resin and a sulfur-containing modified compound, and then a defoamer, a wetting dispersant, a flaky filler, a phosphate, a pigment filler and a composite functional rheological agent are sequentially added thereto, and the coating is obtained after stirring evenly. The weather resistance of the coating formed by the coating disclosed in the patent is greatly improved, the adhesion is enhanced, and the recoating time is extended. However, the coating surface prepared by the patent does not have super-hydrophobic properties, and the preparation process is cumbersome and the preparation time is long.

[0004] The Chinese patent of publication number CN117106352A discloses a modified coating, a method for preparing a recoatable coating with a hydrophilic-hydrophobic conversion property, in which hydrophobic nano-silica is first filled into at least one of a silicone-acrylic emulsion and a fluorinated acrylate, and then a surfactant with a sulfonic acid group at the end is added, stirred evenly and diluted to obtain a hydrophobic coating by spraying. The preparation method disclosed in the patent is simple, and secondary coating of the coating can be achieved. However, the coating disclosed in the patent introduces a fluorinated group in its preparation process, which is prone to environmental pollution.

[0005] The Chinese patent of publication number CN118389015A discloses a method for preparing a water-based low surface energy recoatable coating, wherein methyltriethoxysilane, water and acetic acid are mixed and heated to obtain pre-hydrolyzed siloxane, and then a hydrophobic inorganic nanoparticle dispersion is added thereto to mix with an acidified acrylate aqueous solution to prepare a water-based low surface energy recoatable coating. The coating prepared by the patent has strong hydrophobicity and excellent recoatability. However, the coating function prepared is single, the substrate is single, and the adhesion and wear resistance are poor, which limits its practical application.

[0006] Although a small number of methods and processes have been used to develop recoatable low surface energy surfaces, the existing preparation methods have problems such as cumbersome preparation processes, lack of green environmental protection, single substrate selection, and limited application range. Therefore, it is more meaningful to develop a multifunctional recoatable long-lasting low surface energy coating that can be applied to a variety of substrates, has a simple preparation method, is green and environmentally friendly, and has stable performance for practical applications. Summary of the invention

[0007] Based on the problems raised by the above-mentioned prior art, the present invention provides a long-lasting low surface energy coating with high recoatability and a preparation method and application thereof. The preparation method is simple in process, mild in conditions, green and environmentally friendly, and does not require complex instruments and equipment. At the same time, the formed coating itself also has good superhydrophobicity, environmental adaptability and pH responsiveness, and is endowed with high recoatability, thereby extending the service life of the coating. When the coating is partially damaged or aged after long-term use, a new coating can also be obtained by recoating.

[0008] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.

[0009] In one aspect, the present invention provides a long-lasting low surface energy coating with high recoatability, which is mainly composed of the following components by weight: 0.1 to 5 parts of inorganic / organic nanoparticles modified by a combination of an alkane treatment agent and an amino treatment agent, 0.2 to 10 parts of a base resin for coating, and 85 to 99.7 parts of an aqueous solvent;

[0010] The alkane-based treating agent and the amino-based treating agent are combined to modify the inorganic / organic nanoparticles, wherein the amino-based treating agent is any one or more compounds in the following structural formulas:

[0011]

[0012] Where R 1 and R 2 H, CH 3 or C 2 H 5 , R is Si(CH 3 O) 3 、Si(C2 H 5 O) 3 , CH 2 =CHCOO, CH 2 =C(CH 3 )COO, SH, OH or Si(CH 3 ) 2 Cl and other active groups that can react with hydroxyl groups;

[0013] The alkane treatment agent is any one or more compounds of the following structural formulas:

[0014]

[0015] Where n≥7, R is Si(CH 3 O) 3 、Si(C 2 H 5 O) 3 , CH 2 =CHCOO, CH 2 =C(CH 3 )COO, SH, OH or Si(CH 3 ) 2 Cl or other active groups that can react with hydroxyl groups, and X is Cl or Br.

[0016] Herein, the inorganic / organic nanoparticles are the hydrophobic nanoparticle fillers conventionally selected for hydrophobic coatings in the prior art, or the hydrophobic nanoparticle fillers selected after modification. Those skilled in the art can know the conventional inorganic / organic nanoparticle fillers that can be used for hydrophobic coatings based on the prior art.

[0017] In order to better illustrate the present invention and provide a technical solution for reference, the inorganic / organic nanoparticles are selected to include any one or more of nano-silicon dioxide, nano-titanium dioxide, nano-zinc oxide, nano-aluminum oxide, nano-magnesium oxide, polyurea-formaldehyde nanoparticles, polystyrene nanoparticles, polyacrylamide nanoparticles, and polymethyl methacrylate nanoparticles.

[0018] In this article, the inorganic / organic nanoparticles modified by the combined use of alkane-based treating agents and amino-based treating agents are the products obtained by modifying the inorganic / organic nanoparticles with two or more different treating agents, and can follow the conventional modification conditions and process operations of silane coupling agents when modifying inorganic / organic nanoparticles.

[0019] In one of the technical solutions, the alkane treatment agent is specifically selected from any one or more of dimethyltetradecyl[3-(trimethoxysilyl)propyl]ammonium chloride, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, dimethyltetradecyl[3-(trimethoxysilyl)propyl]ammonium bromide, and dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium bromide.

[0020] In one of the technical solutions, the amino-based treating agent is specifically selected from any one or more of (N,N-dimethyl-3-aminopropyl)trimethoxysilane, (N-methyl-3-aminopropyl)trimethoxysilane, (3-aminopropyl)trimethoxysilane, and (N,N-diethyl-3-aminopropyl)trimethoxysilane.

[0021] It should be noted that when the alkane-based treating agent and the amino-based treating agent are jointly modified, their addition ratio, modification conditions and process operations can all follow the common knowledge methods in the art, or the relevant instructions for use of the specific selected treating agent or the methods of use recorded in existing literature.

[0022] In order to better illustrate the present invention and provide a technical solution for reference, the mass ratio of the alkane treatment agent to the inorganic / organic nanoparticles is (8-95):100; the mass ratio of the amino treatment agent to the inorganic / organic nanoparticles is (26-65):100.

[0023] In one of the more preferred technical solutions, the mass ratio of the alkane treatment agent to the inorganic / organic nanoparticles is (8-47):100; the mass ratio of the amino treatment agent to the inorganic / organic nanoparticles is (45-65):100.

[0024] It should be emphasized that when the alkane-based treating agent and the amino-based treating agent are jointly modified, the modification conditions and process operations can all follow the common knowledge methods in the art. Therefore, the technical scheme provided below in the present invention does not mean the sole designation or limitation of the preparation method of inorganic / organic nanoparticles jointly modified by the alkane-based treating agent and the amino-based treating agent.

[0025] In one preferred technical solution, the preparation method of inorganic / organic nanoparticles modified by the combined use of an alkane-based treatment agent and an amino-based treatment agent mainly comprises the following steps:

[0026] The alkane treatment agent, the amino treatment agent and the inorganic / organic nanoparticles are dispersed in solvent A, stirred for reaction for 12 to 48 hours, separated, washed and dried to obtain inorganic / organic nanoparticles modified by the alkane treatment agent and the amino treatment agent.

[0027] In the above technical solution, solvent A is a conventional solvent selected when a silane coupling agent is used to modify inorganic / organic nanoparticles, such as anhydrous ethanol, n-hexane, cyclohexane, dichloromethane, n-heptane, n-octane, acetone, benzene, toluene, and ethyl acetate; more preferably, the solvent A is a mixed solution of ethanol and water in a mass ratio of (25-75): (25-75). Usually, the amount of solvent A used is in a material-liquid mass ratio of 1: (50-150).

[0028] In this article, the base resin for the coating is a conventional resin selected as a base material in a hydrophobic coating, such as any one of epoxy resin, silicone resin, polyacrylic resin, polyurethane, and urea-formaldehyde resin.

[0029] In this article, the aqueous solvent is selected as a conventional aqueous solvent in a hydrophobic coating, but it should be noted that because the alkane treatment agent and the amino treatment agent jointly modify the inorganic / organic nanoparticles, they have the characteristics of hydrophilic-hydrophobic conversion, and show super-hydrophobic properties in a non-acidic environment. If they are directly blended with non-acidic solvents, it will lead to the inability to disperse evenly. Therefore, in the actual preparation of the long-lasting low surface energy coating step, the alkane treatment agent and the amino treatment agent jointly modify the inorganic / organic nanoparticles in an acidic solution, and then add an alkaline solution to mix and restore to neutrality after mixing evenly, and then add a coating base resin to mix evenly, that is, a long-lasting low surface energy coating with high recoatability is obtained. However, it should be noted that because it is finally restored to neutrality, from the perspective of the constituent components, its essence is still a conventional neutral aqueous solvent.

[0030] In one of the technical solutions, in order to ensure its full dispersion, the aqueous solvent is a neutral solvent mixed with an acidic aqueous solution with a pH of 1 to 3 and an alkaline aqueous solution with a pH of 11 to 13; for example, any one or more of a sulfuric acid aqueous solution, a hydrochloric acid aqueous solution, and an acetic acid aqueous solution with a pH of 1 to 3, or any one or more of a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, and a sodium carbonate aqueous solution with a pH of 11 to 13.

[0031] On the other hand, the preparation method of the above-mentioned long-lasting low surface energy coating with high recoatability mainly includes the following steps: dispersing inorganic / organic nanoparticles modified by a combined alkane treatment agent and an amino treatment agent in an acidic aqueous solution, mixing them evenly, then adding an alkaline aqueous solution to mix them back to neutrality, and then adding a coating base resin to mix evenly to obtain a long-lasting low surface energy coating with high recoatability.

[0032] In one preferred technical solution, the raw materials of the highly recoatable long-lasting low surface energy coating further include, by weight:

[0033] 1 to 25 parts of additives.

[0034] Wherein, the additive is one or more combinations of pigment, tackifier, defoamer, leveling agent, antioxidant and rust inhibitor. Generally, the above-mentioned pigment, tackifier, defoamer, leveling agent, antioxidant and rust inhibitor are well-known and commonly used.

[0035] In one of the more preferred technical solutions, in order to further improve the comprehensive performance, the mass ratio of the inorganic / organic nanoparticles modified by the alkane treatment agent and the amino treatment agent to the base resin for the coating is 1: (1 to 5) for the long-lasting low surface energy coating with high recoatability.

[0036] It should be noted that the long-lasting low surface energy coating provided by the present invention follows the conventional coating method of hydrophobic coating in the chemical industry. For example, after a layer of adhesive is coated on a substrate with a smooth surface, the long-lasting low surface energy coating is coated on the surface, and after drying, a long-lasting low surface energy coating with high recoatability can be obtained; or it can be directly coated on the surface of the substrate.

[0037] Typically, the coating method is one of spraying, brushing, and dipping; the adhesive includes but is not limited to 3M adhesive, common coating resin adhesive, inorganic adhesive, etc.; the substrate base material is any one of concrete, glass, wood, stainless steel, copper, iron, aluminum, polyvinylidene fluoride film, polyethylene terephthalate film, cellulose film, polyurethane foam, sponge, cement board, ceramics, textiles or paper products.

[0038] In another aspect, the present invention also provides a method for recoating the above-mentioned long-lasting low surface energy coating with high recoatability, which mainly comprises the following steps:

[0039] The coating formed by the long-lasting low surface energy coating with high recoatability is contacted with an acidic solution with a pH value of 1 to 3. After at least 30 seconds, the long-lasting low surface energy coating with high recoatability is coated on the contact part, and recoating is achieved after drying.

[0040] In this article, the separation, washing and drying are all common knowledge operations in the art. In industrial scale-up, those skilled in the art can choose a more appropriate process operation mode.

[0041] Herein, the stirring reaction is a stirring reaction conventionally used in the art, including magnetic stirring or mechanical stirring, and those skilled in the art can select a suitable stirring reaction mode according to the production scale or the current process conditions. In one technical solution, the stirring reaction can be carried out at a stirring rate of 100 to 300 rpm.

[0042] The present invention has the following beneficial effects:

[0043] (1) In a long-lasting low surface energy coating with high recoatability provided by the present invention, an alkane-based treatment agent and an amino-based treatment agent are used to jointly modify inorganic / organic nanoparticles, thereby constructing a micro-nano structure on the surface of the formed coating and introducing a hydrophilic-hydrophobic conversion structure on the other hand, thereby providing excellent superhydrophobic performance and pH responsiveness, with a static water contact angle of more than 150° and a rolling angle of less than 10°. Furthermore, the surface water contact angle can be reversibly switched under acid-base stimulation, thereby utilizing this reversible switching to achieve recoatability of the old coating.

[0044] (2) The alkane-based treatment agent and the amino-based treatment agent proposed in the present invention are used to jointly modify the inorganic / organic nanoparticles. Both the alkane-based treatment agent and the amino-based treatment agent used contain trimethoxysilylpropyl groups. During the modification process, the trimethoxysilylpropyl groups undergo hydrolysis and condensation reactions with the hydroxyl groups on the surface of the inorganic / organic nanoparticles. The formed silicon-oxygen covalent bonds are stably and tightly connected to the inorganic / organic nanoparticles, thereby ensuring the superhydrophobic stability of the coating.

[0045] (3) The present invention provides a long-lasting low surface energy coating with high recoatability. By adding a coating base resin into the coating, it not only provides better interfacial adhesion, but also provides better environmental adaptability and better mechanical / physical / chemical stability, and can be applied to a variety of substrates.

[0046] (4) The present invention provides a long-lasting low surface energy coating with high recoatability, which achieves the best technical effect through the specific selection of the coating component content ratio: if the alkane treatment agent and the amino treatment agent jointly modify the inorganic / organic nanoparticles and the coating base resin above the mass percentage range proposed in the present invention, it will cause them to fail to disperse evenly to form a uniform system, resulting in uneven spraying and failure to achieve the ideal effect; if the amount of the alkane treatment agent and the amino treatment agent is lower than the mass percentage range proposed in the present invention, the resulting coating has only a certain environmental adaptability and does not have super hydrophobicity, pH responsiveness and recoatability.

[0047] (5) The alkane-based treatment agent and the amino-based treatment agent proposed in the present invention are combined to modify the inorganic / organic nanoparticles. Through specific selection, the best technical effect is achieved and they can fully react with the inorganic / organic nanoparticles.

[0048] (6) The coating has a simple preparation method, and the entire process is carried out at room temperature and pressure. There is no complex chemical reaction, and no toxic by-products are produced. The entire preparation process is green and environmentally friendly, and does not require complex and expensive instruments and equipment. It can be prepared and produced on a large scale at a low cost. It has a wide range of practical application value and is conducive to industrial application and promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1This is the FT-IR graph of the silica nanoparticles modified by the alkane-based treating agent and the amino-based treating agent obtained in step (1) of Example 1 of the present invention.

[0050] Figure 2 This is a SEM scanning electron microscope image of the surface microstructure of the long-lasting low surface energy coating with high recoatability obtained in Example 1 of the present invention.

[0051] Figure 3 This is a test diagram of the static contact angle and rolling angle of the long-lasting low surface energy coating with high recoatability obtained in Example 2 of the present invention to water.

[0052] Figure 4 This is a bar graph showing the static contact angle test results of the long-lasting low surface energy coating with high recoatability obtained in Example 3 of the present invention to water, seawater, coffee, cola, tea, and milk.

[0053] Figure 5 This is a graph showing the change in water contact angle with the number of abrasion times during the abrasion process of the long-lasting low surface energy coating with high recoatability obtained in Example 4 of the present invention using 2000-grit sandpaper under a load of 200 g.

[0054] Figure 6 This is a test chart of the wettability of the long-lasting low surface energy coating with high recoatability obtained in Example 6 of the present invention to different surfaces of acidic, neutral and alkaline droplets.

[0055] Figure 7 This is a bar chart comparing the interfacial adhesion of the long-lasting low surface energy coating with high recoatability obtained in Example 7 of the present invention before and after recoating.

[0056] Figure 8 This is a bar graph comparing the static contact angles of the long-lasting low surface energy coatings with high recoatability obtained in Examples 1 to 8 of the present invention under acidic and neutral droplet conditions. DETAILED DESCRIPTION

[0057] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.

[0058] In one aspect, the present invention provides a long-lasting low surface energy coating with high recoatability, which is mainly composed of the following components by weight: 0.1 to 5 parts of inorganic / organic nanoparticles modified by a combination of an alkane treatment agent and an amino treatment agent, 0.2 to 10 parts of a base resin for coating, and 85 to 99.7 parts of an aqueous solvent;

[0059] The alkane-based treating agent and the amino-based treating agent are combined to modify the inorganic / organic nanoparticles, wherein the amino-based treating agent is any one or more compounds in the following structural formulas:

[0060]

[0061] Where R 1 and R 2 H, CH 3 or C 2 H 5 , R is Si(CH 3 O) 3 、Si(C 2 H 5 O) 3 , CH 2 =CHCOO, CH 2 =C(CH 3 )COO, SH, OH or Si(CH 3 ) 2 Cl and other active groups that can react with hydroxyl groups;

[0062] The alkane treatment agent is any one or more compounds of the following structural formulas:

[0063]

[0064] Where n≥7, R is Si(CH 3 O) 3 、Si(C 2 H 5 O) 3 , CH 2 =CHCOO, CH 2 =C(CH 3 )COO, SH, OH or Si(CH 3 ) 2 Cl or other active groups that can react with hydroxyl groups, and X is Cl or Br.

[0065] Herein, the inorganic / organic nanoparticles are the hydrophobic nanoparticle fillers conventionally selected for hydrophobic coatings in the prior art, or the hydrophobic nanoparticle fillers selected after modification. Those skilled in the art can know the conventional inorganic / organic nanoparticle fillers that can be used for hydrophobic coatings based on the prior art.

[0066] In order to better illustrate the present invention and provide an implementation method for reference, the inorganic / organic nanoparticles are selected to include any one or more of nano-silicon dioxide, nano-titanium dioxide, nano-zinc oxide, nano-aluminum oxide, nano-magnesium oxide, polyurea-formaldehyde nanoparticles, polystyrene nanoparticles, polyacrylamide nanoparticles, and polymethyl methacrylate nanoparticles.

[0067] In this article, the inorganic / organic nanoparticles modified by the combined use of alkane-based treating agents and amino-based treating agents are the products obtained by modifying the inorganic / organic nanoparticles with two or more different treating agents, and can follow the conventional modification conditions and process operations of silane coupling agents when modifying inorganic / organic nanoparticles.

[0068] In one embodiment, the alkane treatment agent is specifically selected to include any one or more of dimethyltetradecyl[3-(trimethoxysilyl)propyl]ammonium chloride, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, dimethyltetradecyl[3-(trimethoxysilyl)propyl]ammonium bromide, and dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium bromide.

[0069] In one embodiment, the amino-based treating agent is specifically selected from any one or more of (N,N-dimethyl-3-aminopropyl)trimethoxysilane, (N-methyl-3-aminopropyl)trimethoxysilane, (3-aminopropyl)trimethoxysilane, and (N,N-diethyl-3-aminopropyl)trimethoxysilane.

[0070] It should be noted that when the alkane-based treating agent and the amino-based treating agent are jointly modified, their addition ratio, modification conditions and process operations can all follow the common knowledge methods in the art, or the relevant instructions for use of the specific selected treating agent or the methods of use recorded in existing literature.

[0071] In order to better illustrate the present invention and provide an embodiment for reference, the mass ratio of the alkane treatment agent to the inorganic / organic nanoparticles is (8-95):100, for example 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100, 15:100, 16:100, 17:100, 18:100, 19:100, 20:100, 21:100, 22:100, 23:100、24:100、25:100、26:100、27:100、28:100、29:100、30:100、31:100、32:100、33:100、34:100、35:100、36:100、37:100、38:100、39:100、40:100、41:100、42:100、43:100、44:100、45:100、46:10 0, 47:100, 48:100, 49:100, 50:100, 55:100, 60:100, 65:100, 70:100, 75:100, 80:100, 85:100, 90:100, 95:100 or any range or point value therebetween; the mass ratio of the amino treatment agent to the inorganic / organic nanoparticles is (26-65):100, for example 26:100, 30:100, 35:100, 4 0:100, 45:100, 46:100, 47:100, 48:100, 49:100, 50:100, 51:100, 52:100, 53:100, 54:100, 55:100, 56:100, 57:100, 58:100, 59:100, 60:100, 61:100, 62:100, 63:100, 64:100, 65:100 or any range or point value in between.

[0072] In one of the more preferred embodiments, the mass ratio of the alkane treatment agent to the inorganic / organic nanoparticles is (8-47):100; the mass ratio of the amino treatment agent to the inorganic / organic nanoparticles is (45-65):100.

[0073] It should be emphasized that when the alkane-based treating agent and the amino-based treating agent are jointly modified, the modification conditions and process operations can all follow the common knowledge methods in the art. Therefore, the technical scheme provided below in the present invention does not mean the sole designation or limitation of the preparation method of inorganic / organic nanoparticles jointly modified by the alkane-based treating agent and the amino-based treating agent.

[0074] In one preferred embodiment, the preparation method of inorganic / organic nanoparticles modified by the combined use of an alkane-based treatment agent and an amino-based treatment agent mainly comprises the following steps:

[0075] The alkane treatment agent, the amino treatment agent and the inorganic / organic nanoparticles are dispersed in solvent A, stirred for reaction for 12 to 48 hours, separated, washed and dried to obtain inorganic / organic nanoparticles modified by the alkane treatment agent and the amino treatment agent.

[0076] In the above embodiment, solvent A is a conventional solvent selected when a silane coupling agent is used to modify inorganic / organic nanoparticles, such as anhydrous ethanol, n-hexane, cyclohexane, dichloromethane, n-heptane, n-octane, acetone, benzene, toluene, and ethyl acetate; more preferably, the solvent A is a mixed solution of ethanol and water in a mass ratio of (25-75): (25-75). Usually, the amount of solvent A used is in a material-liquid mass ratio of 1: (50-150).

[0077] Herein, the base resin for the coating is a conventional resin selected as a base material in a hydrophobic coating, and in one embodiment, it is any one of epoxy resin, silicone resin, polyacrylic resin, polyurethane, and urea-formaldehyde resin.

[0078] In this article, the aqueous solvent is selected as a conventional aqueous solvent in a hydrophobic coating, but it should be noted that because the alkane treatment agent and the amino treatment agent jointly modify the inorganic / organic nanoparticles, they have the characteristics of hydrophilic-hydrophobic conversion, and show super-hydrophobic properties in a non-acidic environment. If they are directly blended with non-acidic solvents, it will lead to the inability to disperse evenly. Therefore, in the actual preparation of the long-lasting low surface energy coating step, the alkane treatment agent and the amino treatment agent jointly modify the inorganic / organic nanoparticles in an acidic solution, and then add an alkaline solution to mix and restore to neutrality after mixing evenly, and then add a coating base resin to mix evenly, that is, a long-lasting low surface energy coating with high recoatability is obtained. However, it should be noted that because it is finally restored to neutrality, from the perspective of the constituent components, its essence is still a conventional neutral aqueous solvent.

[0079] In one embodiment, in order to ensure its full dispersion, the aqueous solvent is a neutral solvent mixed with an acidic aqueous solution with a pH of 1 to 3 and an alkaline aqueous solution with a pH of 11 to 13; for example, any one or more of a sulfuric acid aqueous solution, a hydrochloric acid aqueous solution, and an acetic acid aqueous solution with a pH of 1 to 3, or any one or more of a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, and a sodium carbonate aqueous solution with a pH of 11 to 13.

[0080] In one embodiment, the 0.1-5 parts of alkane treatment agent and amino treatment agent are combined to modify inorganic / organic nanoparticles, such as 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.8 parts, 1 parts, 1.1 parts, 1.2 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 4.8 parts, 5 parts or any range or point value therebetween; the 0.2-10 parts of coating base resin, such as 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 4.8 parts, 5 parts or any range or point value therebetween. , 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts or any range or point value therebetween; 85 to 99.7 parts of an aqueous solvent, for example 85, 85.1, 85.2, 85.3, 85.4, 85.5, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 99.1, 99.2, 99.3, 99.4, 99.5, 99.6, 99.7 parts or any range or point value therebetween.

[0081] On the other hand, the preparation method of the above-mentioned long-lasting low surface energy coating with high recoatability mainly includes the following steps: dispersing inorganic / organic nanoparticles modified by a combined alkane treatment agent and an amino treatment agent in an acidic aqueous solution, mixing them evenly, then adding an alkaline aqueous solution to mix them back to neutrality, and then adding a coating base resin to mix evenly to obtain a long-lasting low surface energy coating with high recoatability.

[0082] In one preferred embodiment, the long-lasting low surface energy coating with high recoatability further comprises, by weight, the following raw materials:

[0083] 1 to 25 parts of additives.

[0084] Wherein, the additive is one or more combinations of pigment, tackifier, defoamer, leveling agent, antioxidant and rust inhibitor. Generally, the above-mentioned pigment, tackifier, defoamer, leveling agent, antioxidant and rust inhibitor are well-known and commonly used.

[0085] In one of the more preferred embodiments, in order to further improve the comprehensive performance, the mass ratio of the highly recoatable long-lasting low surface energy coating, the inorganic / organic nanoparticles modified by the alkane treatment agent and the amino treatment agent to the coating base resin is 1:(1-5), for example, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5 or any range or point value therebetween.

[0086] It should be noted that the long-lasting low surface energy coating provided by the present invention follows the conventional coating method of hydrophobic coating in the chemical industry. For example, after a layer of adhesive is coated on a substrate with a smooth surface, the long-lasting low surface energy coating is coated on the surface, and after drying, a long-lasting low surface energy coating with high recoatability can be obtained; or it can be directly coated on the surface of the substrate.

[0087] Typically, the coating method is one of spraying, brushing, and dipping; the adhesive includes but is not limited to 3M adhesive, common coating resin adhesive, inorganic adhesive, etc.; the substrate base material is any one of concrete, glass, wood, stainless steel, copper, iron, aluminum, polyvinylidene fluoride film, polyethylene terephthalate film, cellulose film, polyurethane foam, sponge, cement board, ceramics, textiles or paper products.

[0088] In another aspect, the present invention also provides a method for recoating the above-mentioned long-lasting low surface energy coating with high recoatability, which mainly comprises the following steps:

[0089] The coating formed by the long-lasting low surface energy coating with high recoatability is contacted with an acidic solution with a pH value of 1 to 3. After at least 30 seconds, the long-lasting low surface energy coating with high recoatability is coated on the contact part, and recoating is achieved after drying.

[0090] In this article, the separation, washing and drying are all common knowledge operations in the art. In industrial scale-up, those skilled in the art can choose a more appropriate process operation mode.

[0091] Herein, the stirring reaction is a stirring reaction conventionally used in the art, including magnetic stirring or mechanical stirring, and those skilled in the art can select a suitable stirring reaction mode according to the production scale or the current process conditions. In one technical solution, the stirring reaction can be carried out at a stirring rate of 100 to 300 rpm.

[0092] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.

[0093] Example

[0094] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.

[0095] 1. Raw materials

[0096] Silica nanoparticles, titanium dioxide nanoparticles, zinc oxide nanoparticles, magnesium oxide nanoparticles, aluminum oxide nanoparticles, and polyurea-formaldehyde nanoparticles were purchased from Shanghai Aladdin Chemical Co., Ltd.

[0097] Dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium bromide, dimethyltetradecyl[3-(trimethoxysilyl)propyl]ammonium chloride and dimethyldodecyl[3-(trimethoxysilyl)propyl]ammonium bromide were provided by Beijing Bailingwei Technology Co., Ltd.

[0098] (N,N-dimethyl-3-aminopropyl)trimethoxysilane, (N-methyl-3-aminopropyl)trimethoxysilane, (N,N-diethyl-3-aminopropyl)trimethoxysilane, and (3-aminopropyl)trimethoxysilane were provided by Beijing Bailingwei Technology Co., Ltd.

[0099] Epoxy resin was provided by Shanghai Dow Chemical Company, polysiloxane resin was provided by Shanghai Wacker Chemical Co., Ltd., and polyurethane was provided by Shanghai MacLean Biochemical Technology Co., Ltd.

[0100] Ethanol, concentrated sulfuric acid, concentrated hydrochloric acid, acetic acid, sodium hydroxide, potassium hydroxide and potassium carbonate were provided by Chengdu Kelong Chemical Industry Reagent Co., Ltd.

[0101] Glass slides were provided by a Chinese glass factory, melamine sponges and polyurethane sponges were provided by a local sponge factory, and commercial concrete, wood, steel plates, plastics, aluminum plates, cotton, coffee, cola, tea, and milk were purchased from local supermarkets.

[0102] 2. Test Method

[0103] (1) The infrared spectra of inorganic / organic nanoparticles modified by alkane-based treatment agents and amino-based treatment agents were tested by Fourier transform infrared spectrometer (FT-IR, Nicolet 6700, Thermo Fisher, USA).

[0104] (2) The microstructure of the coating surface was observed by scanning electron microscopy (SEM, Philips XL-3, FEI Co., USA).

[0105] (3) The hydrophobicity of the coating surface was tested by a contact angle tester (Zhongchen digital equipment Co. Ltd Shanghai, China).

[0106] (4) Referring to the test method in GB / T 5210-2006, place a sample with a size of 150×70 mm in an environment with a temperature of (23±2)℃ and a relative humidity of (50±5)%; then fix a test column (bottom diameter of 30 mm) coated with adhesive on the surface to the sample surface. After the adhesive is cured, immediately place the test combination under a tensile testing machine, apply tensile stress in a direction perpendicular to the plane of the sample, and record the tensile force that destroys the test combination. The destructive strength can be expressed by the following formula, measured in MPa:

[0107] σ=F / A

[0108] (Where: F is the destructive force, unit is N; A is the test column area, unit is mm 2 )

[0109] The test was repeated three times and the average value was taken as the adhesion strength.

[0110] Example 1

[0111] Embodiment 1 provides a method for preparing a long-lasting low surface energy coating with high recoatability, which specifically comprises the following steps:

[0112] (1) Preparation of inorganic / organic nanoparticles modified by alkane-based treatment agents and amino-based treatment agents: 0.5 g of silica nanoparticles with a size of about 30 nanometers were dispersed in a mixed solution of 24 g of water and 25.06 g of anhydrous ethanol, and then 0.13 g of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and 0.31 g of (N,N-dimethyl-3-aminopropyl)trimethoxysilane were added. After stirring for 24 hours, the mixture was separated and washed to obtain silica nanoparticles modified by alkane-based treatment agents and amino-based treatment agents. Figure 1 As shown in the FT-IR graph of the silica nanoparticles modified by the alkane-based treating agent and the amino-based treating agent obtained in this example, at 2930 / 2854 cm- 1 The peak is the position of the CH stretching vibration peak, at 1448cm- 1 The peak is the bending vibration peak of CH, at 473cm- 1 , 804cm- 1 and 1107cm- 1 The peaks are all Si-O peaks, proving the successful synthesis of modified inorganic / organic nanoparticles.

[0113] (2) Preparation of a long-lasting low surface energy coating with high recoatability: 0.1 g of silica nanoparticles modified by the alkane treatment agent and the amino treatment agent obtained in step (1) was dispersed in 49.75 g of an acid solution with a pH of 1, and after mixing evenly, 49.75 g of an alkaline solution with a pH of 13 was added. After stirring for 5 min, 0.4 g of an aqueous epoxy resin (Ep) was added, and finally mixed evenly to obtain a long-lasting low surface energy coating with high recoatability.

[0114] For the convenience of testing, the long-lasting low surface energy coating obtained in step (2) is sprayed onto the concrete surface and dried at room temperature to obtain a long-lasting low surface energy coating with high recoatability.

[0115] like Figure 2 As shown in the SEM image of the surface of the long-lasting low surface energy coating obtained in this embodiment, the water contact angle of the surface is 155.3° and the rolling angle is 1.3°. In addition, the concrete substrate in this embodiment can also be replaced by other substrates with smooth surfaces such as glass, iron sheet, wood, aluminum sheet, etc.

[0116] Example 2

[0117] Embodiment 2 provides a method for preparing a long-lasting low surface energy coating with high recoatability, which specifically comprises the following steps:

[0118] (1) Preparation of inorganic / organic nanoparticles modified by an alkane-based treatment agent and an amino-based treatment agent: 0.67 g of titanium dioxide nanoparticles with a size of about 15 nanometers were dispersed in a mixed solution of 23 g of water and 25.93 g of anhydrous ethanol, and then 0.07 g of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium bromide and 0.33 g of (N,N-dimethyl-3-aminopropyl)trimethoxysilane were added. After stirring for 36 hours, the mixture was separated and washed to obtain titanium dioxide nanoparticles modified by an alkane-based treatment agent and an amino-based treatment agent.

[0119] (2) Preparation of a long-lasting low surface energy coating with high recoatability: 0.11 g of titanium dioxide nanoparticles modified by the alkane treatment agent and the amino treatment agent obtained in step (1) were dispersed in 39.72 g of an acid solution with a pH of 1, and after mixing, 39.72 g of an alkaline solution with a pH of 13 was added. After stirring for 5 minutes, 0.45 g of a water-based epoxy resin (Ep) was added, and after mixing, a long-lasting low surface energy coating with high recoatability was obtained.

[0120] For the convenience of testing, the long-lasting low surface energy coating obtained in step (2) is sprayed onto the surface of printing paper, and after drying, a long-lasting low surface energy coating with high recoatability is obtained.

[0121] like Figure 3As shown in the contact angle test result of the long-lasting low surface energy coating obtained in this embodiment, its contact angle to water reaches 154.5° and the rolling angle is 1.7°. In addition, the printing paper substrate in this embodiment can also be replaced by other substrates with rough surfaces such as wood, filter paper, textiles, cellulose membranes, etc.

[0122] Example 3

[0123] Embodiment 3 provides a method for preparing a long-lasting low surface energy coating with high recoatability, which specifically comprises the following steps:

[0124] (1) Preparation of inorganic / organic nanoparticles modified by alkane-based treatment agents and amino-based treatment agents: 1 g of aluminum oxide nanoparticles with a size of about 30 nanometers was added to a mixed solution of 48.62 g of water and 50 g of anhydrous ethanol, and then 0.1 g of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and 0.28 g of [3-(N,N-dimethylamino)propyl]trimethoxysilane were added. The mixture was stirred for 36 hours and then separated and washed to obtain aluminum oxide nanoparticles modified by alkane-based treatment agents and amino-based treatment agents.

[0125] (2) Preparation of a long-lasting low surface energy coating with high recoatability: 2.0 g of the alkane treatment agent and the amino treatment agent obtained in step (1) are combined with modified aluminum oxide nanoparticles and dispersed in 23.5 g of an acid solution with a pH of 1. After mixing, 23.5 g of an alkaline solution with a pH of 13 is added. After stirring for 5 minutes, 1.0 g of a polysiloxane resin (PSi) is added. After mixing, a long-lasting low surface energy coating with high recoatability is obtained.

[0126] For the convenience of testing, the long-lasting low surface energy coating obtained in step (2) is sprayed onto the fabric surface, and after drying, a long-lasting low surface energy coating with high recoatability is obtained.

[0127] like Figure 4 As shown, the contact angle of the long-lasting low surface energy coating obtained in this embodiment to water reaches 154.0°, and its static contact angle to common seawater, coffee, cola, tea, and milk in life can also exceed 150°. In daily life, it can prevent contamination by liquid pollutants such as seawater, coffee, cola, tea, and milk, and has a self-cleaning effect on solid pollutants such as dust and copper sulfate. At the same time, if the fabric coating is contaminated by castor oil, most of the oil stains on the coating surface can be effectively removed by stirring and washing in an acidic solution, which has a decontamination effect.

[0128] Example 4

[0129] Embodiment 4 provides a method for preparing a long-lasting low surface energy coating with high recoatability, which specifically comprises the following steps:

[0130] (1) Preparation of inorganic / organic nanoparticles modified by an alkane-based treatment agent and an amino-based treatment agent: 0.5 g of silica nanoparticles with a size of about 15 nanometers were dispersed in a mixed solution of 36.81 g of water and 12.3 g of anhydrous ethanol, and then 0.07 g of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and 0.32 g of (N,N-dimethyl-3-aminopropyl)trimethoxysilane were added. After stirring for 24 hours, the mixture was separated and washed to obtain silica nanoparticles modified by an alkane-based treatment agent and an amino-based treatment agent.

[0131] (2) Preparation of a long-lasting low-surface-energy coating with high recoatability: 0.2 g of the silica nanoparticles modified by the alkane-based treatment agent and the amino-based treatment agent obtained in step (1) were dispersed in 10 g of an acid solution of pH=1, mixed evenly, and then 10 g of an alkaline solution of pH=13 was added, stirred for 5 min, and then 0.5 g of a polysiloxane resin (PSi) was added, and mixed evenly to obtain a long-lasting low-surface-energy coating with high recoatability. For the convenience of testing, the long-lasting low-surface-energy coating obtained in step (2) was sprayed onto the glass surface, and dried at room temperature to obtain a long-lasting low-surface-energy coating with high recoatability.

[0132] The long-lasting low surface energy coating obtained in this example has a water contact angle of 153.0° and a rolling angle of 2.1°. Due to the strong adhesion of the epoxy resin, the coating has good mechanical stability. Figure 5 As shown, the surface wetting performance of the coating after 100 (20 m) sandpaper abrasion cycles.

[0133] Example 5

[0134] Example 5 provides a method for preparing a long-lasting low surface energy coating with high recoatability, which specifically comprises the following steps:

[0135] (1) Preparation of inorganic / organic nanoparticles modified by alkane-based treatment agents and amino-based treatment agents: 0.5 g of magnesium oxide nanoparticles with a size of about 10 nanometers and 0.5 g of aluminum oxide nanoparticles with a size of about 1 nanometer were mixed and dispersed in a mixed solution of 24.86 g of water and 73.38 g of anhydrous ethanol. Then, 0.18 g of dimethyldodecyl[3-(trimethoxysilyl)propyl]ammonium bromide and 0.18 g of dimethyltetradecyl[3-(trimethoxysilyl)propyl]ammonium bromide, two mixed alkane-based treatment agents, were added. 0.4 g of (3-aminopropyl)trimethoxysilane was added. After stirring for 96 hours, the zinc oxide and aluminum oxide nanoparticles modified by the alkane-based treatment agent and the amino-based treatment agent were obtained by separation and washing.

[0136] (2) Preparation of a long-lasting low surface energy coating with high recoatability: 2 g of zinc oxide and aluminum oxide nanoparticles modified by the alkane treatment agent and the amino treatment agent obtained in step (1) are dispersed in 17 g of an acid solution with a pH of 1, and after mixing, 17 g of an alkaline solution with a pH of 13 is added. After stirring for 5 minutes, 2 g of a polysiloxane resin (PSi) and 2 g of a polyurethane are added, and after mixing, a long-lasting low surface energy coating with high recoatability is obtained.

[0137] For the convenience of testing, the long-lasting low surface energy coating obtained in step (2) is applied to the surface of the polyurethane foam by dipping, and after drying, a long-lasting low surface energy coating with high recoatability is obtained.

[0138] The long-lasting low surface energy coating obtained in this embodiment has a water contact angle of 154.8° and a rolling angle of 3.2°. In addition, the polyurethane foam substrate in this embodiment can also be replaced by other loose and porous substrates such as melamine sponge, polyurethane sponge, cotton, etc.

[0139] Example 6

[0140] Example 6 provides a method for preparing a long-lasting low surface energy coating with high recoatability, which specifically comprises the following steps:

[0141] (1) Preparation of inorganic / organic nanoparticles modified by alkane-based treatment agents and amino-based treatment agents: 0.5 g of zinc oxide particles with a size of about 10 nanometers and 1.5 g of polyurea-formaldehyde nanoparticles with a size of about 100 nanometers were mixed and dispersed together in a mixed solution of 20.84 g of water and 25 g of anhydrous ethanol, and then a mixture of 0.52 g of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, 0.62 g of (N,N-dimethyl-3-aminopropyl)trimethoxysilane and 0.64 g of (N,N-diethyl-3-aminopropyl)trimethoxysilane was added. After stirring for 72 hours, the mixture was separated and washed to obtain zinc oxide and polyurea-formaldehyde nanoparticles modified by alkane-based treatment agents and amino-based treatment agents.

[0142] (2) Preparation of a long-lasting low surface energy coating with high recoatability: 2 g of zinc oxide and polyurea-formaldehyde nanoparticles modified by the alkane treatment agent and the amino treatment agent obtained in step (1) are dispersed in 45 g of an acid solution with a pH of 1, and after mixing, 45 g of an alkaline solution with a pH of 13 is added. After stirring for 5 minutes, 8 g of epoxy resin (Ep) is added, and after mixing, a long-lasting low surface energy coating with high recoatability is obtained.

[0143] For the convenience of testing, the long-lasting low surface energy coating obtained in step (2) is sprayed onto the concrete surface and dried at room temperature to obtain a long-lasting low surface energy coating with high recoatability.

[0144] like Figure 6 As shown, the long-lasting low surface energy coating obtained in this embodiment has an acidic droplet contact angle of 0° on its surface, showing a hydrophilic state; the neutral droplet and the alkaline droplet have a contact angle of more than 150° on the surface, showing a super-hydrophobic state. In addition, the concrete substrate in this example can also be replaced by other substrates with smooth surfaces such as glass and wood.

[0145] Example 7

[0146] Example 7 provides a method for preparing a long-lasting low surface energy coating with high recoatability, which specifically comprises the following steps:

[0147] (1) Preparation of inorganic / organic nanoparticles modified by alkane-based treatment agents and amino-based treatment agents: 1.5 g of silica nanoparticles with a size of about 100 nanometers were dispersed in a mixed solution of 47.39 g of water and 50 g of anhydrous ethanol, and then two mixed alkane-based treatment agents, 0.32 g of dimethyltetradecyl[3-(trimethoxysilyl)propyl]ammonium chloride and 0.17 g of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium bromide, and 0.62 g of (N-methyl-3-aminopropyl)trimethoxysilane were added. After stirring for 32 hours, the silica nanoparticles modified by the alkane-based treatment agent and the amino-based treatment agent were obtained by separation and washing.

[0148] (2) Preparation of a long-lasting low surface energy coating with high recoatability: 1.0 g of silica nanoparticles modified by the alkane treatment agent and the amino treatment agent obtained in step (1) was dispersed in 23.25 g of an acid solution with a pH of 1, and after mixing, 23.25 g of an alkaline solution with a pH of 13 was added. After stirring for 5 minutes, 2.5 g of a polysiloxane resin (PSi) was added, and after mixing, a long-lasting low surface energy coating with high recoatability was obtained.

[0149] For the convenience of testing, the long-lasting low surface energy coating obtained in step (2) is sprayed onto the concrete surface and dried at room temperature to obtain a long-lasting low surface energy coating with high recoatability.

[0150] like Figure 7 As shown, the long-lasting low surface energy coating obtained in this embodiment has an adhesion of 5.22 MPa; after recoating, the adhesion is still 5.34 MPa. In addition, the concrete substrate in this example can also be replaced by other substrates with smooth surfaces such as glass and wood.

[0151] Example 8

[0152] Example 8 provides a method for preparing a long-lasting low surface energy coating with high recoatability, which specifically comprises the following steps:

[0153] (1) Preparation of inorganic / organic nanoparticles modified by an alkane-based treatment agent and an amino-based treatment agent: 0.5 g of silica nanoparticles with a size of about 30 nanometers were dispersed in a mixed solution of 24 g of water and 24.8 g of anhydrous ethanol, and then 0.39 g of dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride and 0.31 g of (N,N-dimethyl-3-aminopropyl)trimethoxysilane were added. After stirring for 24 hours, the mixture was separated and washed to obtain silica nanoparticles modified by an alkane-based treatment agent and an amino-based treatment agent.

[0154] (2) Preparation of a long-lasting low surface energy coating with high recoatability: 0.1 g of silica nanoparticles modified by the alkane treatment agent and the amino treatment agent obtained in step (1) was dispersed in 49.75 g of an acid solution with a pH of 1, and after mixing evenly, 49.75 g of an alkaline solution with a pH of 13 was added. After stirring for 5 min, 0.4 g of a water-based epoxy resin (Ep) was added, and finally mixed evenly to obtain a long-lasting low surface energy coating with high recoatability.

[0155] For the convenience of testing, the long-lasting low surface energy coating obtained in step (2) is sprayed onto the concrete surface and dried at room temperature to obtain a long-lasting low surface energy coating with high recoatability.

[0156] The long-lasting low surface energy coating obtained in this embodiment has a surface contact angle of 148.83° for acidic droplets, showing a hydrophobic state; the surface contact angle of neutral droplets is 154.25°, showing a super-hydrophobic state. Compared with Example 1, although the coating of this embodiment still exhibits different surface wettabilities in acidic and neutral environments, it is unable to achieve a good switching between the hydrophilic and hydrophobic states of the surface, and the recoating performance is extremely poor.

[0157] like Figure 8 As shown, the static contact angles of the long-lasting low surface energy coatings obtained in Examples 1 to 8 under acidic and neutral droplet conditions were compared horizontally, and it was found that during the coating preparation process, the final long-lasting low surface energy coatings exhibited different hydrophilic-hydrophobic conversion characteristics at different ratios of alkane treatment agents, amino treatment agents and inorganic / organic nanoparticles, among which Example 1 and Example 6 had the best comprehensive performance.

[0158] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A long-lasting low surface energy coating with high recoatability, characterized in that The invention mainly consists of the following components by weight: 0.1 to 5 parts of inorganic / organic nanoparticles modified by a combination of an alkane treatment agent and an amino treatment agent, 0.2 to 10 parts of a base resin for coatings and 85 to 99.7 parts of an aqueous solvent.

2. The long-lasting low surface energy coating according to claim 1, characterized in that: The alkane-based treating agent and the amino-based treating agent are combined to modify the inorganic / organic nanoparticles, wherein the amino-based treating agent is any one or more compounds in the following structural formulas: Wherein R1 and R2 are H, CH3 or C2H5 respectively, and R is Si(CH3O)3, Si(C2H5O)3, CH2=CHCOO, CH2=C(CH3)COO, SH, OH or Si(CH3)2Cl; The alkane treatment agent is any one or more compounds of the following structural formulas: In the formula, n≥7, R is Si(CH3O)3, Si(C2H5O)3, CH2=CHCOO, CH2=C(CH3)COO, SH, OH or Si(CH3)2Cl, and X is Cl or Br.

3. The long-lasting low surface energy coating according to claim 1, characterized in that: The inorganic / organic nanoparticles include any one or more of nano-silicon dioxide, nano-titanium dioxide, nano-zinc oxide, nano-aluminum oxide, nano-magnesium oxide, polyurea-formaldehyde nanoparticles, polystyrene nanoparticles, polyacrylamide nanoparticles, and polymethyl methacrylate nanoparticles.

4. The long-lasting low surface energy coating according to claim 1, characterized in that: The alkane-based treating agent includes any one or more of dimethyltetradecyl[3-(trimethoxysilyl)propyl]ammonium chloride, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, dimethyltetradecyl[3-(trimethoxysilyl)propyl]ammonium bromide, and dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium bromide; the amino-based treating agent includes any one or more of (N,N-dimethyl-3-aminopropyl)trimethoxysilane, (N-methyl-3-aminopropyl)trimethoxysilane, (3-aminopropyl)trimethoxysilane, and (N,N-diethyl-3-aminopropyl)trimethoxysilane.

5. The long-lasting low surface energy coating according to claim 1, characterized in that: The mass ratio of the alkane treatment agent to the inorganic / organic nanoparticles is (8-95):100; the mass ratio of the amino treatment agent to the inorganic / organic nanoparticles is (26-65):

100.

6. The long-lasting low surface energy coating according to claim 1, characterized in that: The preparation method of inorganic / organic nanoparticles modified by a combined alkane treatment agent and an amino treatment agent mainly comprises the following steps: The alkane treatment agent, the amino treatment agent and the inorganic / organic nanoparticles are dispersed in solvent A, stirred for reaction for 12 to 48 hours, separated, washed and dried to obtain inorganic / organic nanoparticles modified by the alkane treatment agent and the amino treatment agent.

7. The long-lasting low surface energy coating according to claim 1, characterized in that: The base resin for the coating includes any one of epoxy resin, silicone resin, polyacrylic resin, polyurethane and urea-formaldehyde resin.

8. The long-lasting low surface energy coating according to claim 1, characterized in that: The aqueous solvent is a neutral solvent formed by mixing an acidic aqueous solution with a pH of 1 to 3 and an alkaline aqueous solution with a pH of 11 to 13.

9. The long-lasting low surface energy coating according to claim 1, characterized in that: The mass ratio of the inorganic / organic nanoparticles modified by the alkane treatment agent and the amino treatment agent to the base resin for coating is 1:(1-5).

10. The application method of the long-lasting low surface energy coating according to claim 1, characterized in that: After a layer of adhesive is applied to a smooth substrate, a long-lasting low surface energy coating is applied to the surface, and after drying, a long-lasting low surface energy coating with high recoatability can be obtained; Or directly coated on the surface of the substrate; The substrate base material is any one of concrete, glass, wood, stainless steel, copper, iron, aluminum, polyvinylidene fluoride film, polyethylene terephthalate film, cellulose film, polyurethane foam, sponge, cement board, ceramics, textiles or paper products.

Citation Information

Patent Citations

  • A recoatable low-viscosity, high-film-thickness vinyl ester coating and its preparation method

    CN110295000B

  • Modified coating, recoated coating with hydrophilic-hydrophobic conversion property, and preparation method and application of coating

    CN117106352A

  • Grafted membranes and substrates having surfaces with switchable superoleophilicity and superoleophobicity and applications thereof

    CA2850442A1

  • Preparation method and applications of super hydrophobic oleophobic material with pH responsiveness

    CN109173345A

  • Fluorine-free antibacterial transparent superhydrophobic coating, preparation method and application thereof

    CN109971295A